Salat Tahajud Berpengaruh terhadap Penurunan Stres Mahasiswa - Azis Ritonga; Bilqis Azizah (Poltekkes Kemenkes Jakarta III, 2018)
Stress is generally intended to determine the conditions that affect a person's physical or psychological state due to external pressure. A student susceptible to stress can produce student academic performance and mental health. One form of stress management by performing Tahajud Prayers. The purpose of this study was to determine the effect of tahajud prayers on stress reduction in physiotherapy students. This research is an experimental quasi research with pretest-posttest non-equivalent control two groups design, with sample consist of 15 experimental group students and 15 control group students at Physiotherapy 2nd year students at Poltekkes Kemenkes Jakarta III. Interventions given were Tahajud Prayers and the stress score was measured using a DASS-42 questionnaire. Statistical analysis t-test independents. In the experimental group the mean value of stress before was 17,2 and after the treated treatment was 6,47. As for the control group the mean value of stress before was 13 and afterwards was 16,4. Hypothesis test using independent sample t-test shows there is difference of stress value between experimental group and control (p = 0,0001). Tahajud Prayers has an influence on stress reduction. Tahajud Prayers is expected to be one of the stress management efforts in physiotherapy services.